English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^2 - 4x +13 = 0

I got x = 2 (+-) sq root of 7

2007-05-07 08:58:33 · 5 answers · asked by confused 1 in Science & Mathematics Mathematics

5 answers

Completing the square

x² - 4x + 13 = 0

x² - 4x + 13 - 13 = 0 - 13

x² - 4x = - 13

x² - 4x +______ = - 13 +______

x² - 4x + 4 = - 13 + 4

(x - 2)(x - 2) = - 9

(x - 2)² = - 9

(√x - 2)² = ± √- 9

x - 2 = ± i√9

x - 2 = ± 3i

x - 2 + 2 = 2 ± 3i

x = 2 ± 3i

- - - - - - - - - s-

2007-05-07 09:47:17 · answer #1 · answered by SAMUEL D 7 · 1 0

ax²+bx+c=0 Here, a = 1, b = −4, and c = 13.

The roots are x = (−b ± √(b²−4ac))÷(2a). Thus the two values of x = [4±√(16-52)]÷2 = [4±√(−36)]÷2 = [4±6i]÷2 = 2 ± 3i, a set of complex roots.

2007-05-07 16:31:16 · answer #2 · answered by engineer01 5 · 0 0

x^2-4x+13 is the same as x^2 - 4x +4 = -9
which can be factored into (x-2)^2 = -9
therefore x-2 = 3i, x = 3i+2

2007-05-07 16:13:51 · answer #3 · answered by Brad K 3 · 0 0

If your equation is correctly typed, it only has complex roots,

x^2 -4x+13 = (x-2)^2+9

thus (x-2)^2=-9, so x=2 (+-) sqrt(-9) = 2(+-) 3i

2007-05-07 16:08:26 · answer #4 · answered by ulfsnilsson 2 · 1 0

I'll tell you that the result is imaginary and that the answer of x is (4+/-6i)/2, 6i is sqrt of -36

2007-05-07 16:09:14 · answer #5 · answered by UnknownD 6 · 1 0

fedest.com, questions and answers